An Analysis of The Application of Medical Rehabilitation & Social Rehabilitation for People Convicted of Drug Abuse - Panjiyoga, Indrawienny; Sudiro, Ahmad (Universitas Islam Sultan Agung, 2024)
The importance of the implementation of rehabilitation for narcotics users is not merely to replace the sentence period, but rehabilitation is intended for narcotics users to cure them from addiction to be free from their dependence on narcotics. The problems faced in this study are how the rehabilitation arrangements for narcotics users based on Law No. 35 of 2009 concerning Narcotics and how the application of medical rehabilitation and social rehabilitation for convicted narcotics abusers in the case of Decision Number 582/Pid.Susof 2021/PN.Jkt.Brt. The research method used in this writing is normative juridical research. The results show that Law No. 35 of 2009 concerning Narcotics pays special attention to rehabilitation efforts for narcotics users. This is based on the understanding that drug abuse is a health and social problem that requires special handling, not merely a legal problem. Law No. 35 of 2009 has provided a strong legal umbrella for the implementation of rehabilitation for people who use drugs. However, there are still many challenges that must be overcome in order for the rehabilitation program to run effectively. In general, based on Law No. 35 of 2009 on Narcotics, specifically Article 54, every drug addict is required to undergo medical and social rehabilitation. This rehabilitation aims to restore the physical and mental condition of drug users and restore their function in society.